Clinical course of infection and viral tissue tropism of hepatitis C virus–like nonprimate hepaciviruses in horses. Issue 2 (5th January 2015) - Pfaender, Stephanie; Cavalleri, Jessika M.V.; Walter, Stephanie; Doerrbecker, Juliane; Campana, Benedetta; Brown, Richard J.P.; Burbelo, Peter D.; Postel, Alexander; Hahn, Kerstin; Anggakusuma; Riebesehl, Nina; Baumgärtner, Wolfgang; et al.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) has a very narrow species and tissue tropism and efficiently replicates only in humans and the chimpanzee. Recently, several studies identified close relatives to HCV in different animal species. Among these novel viruses, the nonprimate hepaciviruses (NPHV) that infect horses are the closest relatives of HCV described to date. In this study, we analyzed the NPHV prevalence in northern Germany and characterized the clinical course of infection and viral tissue tropism to explore the relevance of HCV‐related horse viruses as a model for HCV infection. We found that approximately 31.4% of 433 horses were seropositive for antibodies (Abs) against NPHV and approximately 2.5% carried viral RNA. Liver function analyses revealed no indication for hepatic impairment in 7 of 11 horses. However, serum gamma‐glutamyl transferase (GGT) concentrations were mildly elevated in 3 horses, and 1 horse displayed even highly elevated GGT levels. Furthermore, we observed that NPHV infection could be cleared in individual horses with a simultaneous emergence of nonstructural (NS)3‐specific Abs and transient elevation of serum levels of liver‐specific enzymes indicative for a hepatic inflammation. In other individual horses, chronic infections could be observed with the copresence of viral RNA and NS3‐specific Abs for over 6 months. For the determination of viral tissue tropism, we analyzed different organs and tissues of 1 NPHV‐positive horse using quantitative real‐time polymerase chain reaction and fluorescent in situ hydridization and detected NPHV RNA mainly in the liver and at lower amounts in other organs. Conclusion: Similar to HCV infections in humans, this work demonstrates acute and chronic stages of NPHV infection in horses with viral RNA detectable predominantly within the liver. (Hepatology 2015;61:448‐459)